Strategi Prouksi Pesawat X Dalam Menghadapi Persaingan Pasar Global - Ridwan, Agus Salim; Adhytiawan, Eri (Warta Penelitian Perhubungan, 2010)
From technologtj side, plane Juzs any advantages with their competitor. Wzereas the advantages arenot mainly guaranteed tlwt that plnn am win from global competition. Buying decision of planbusiness depend on perfomuznce factors, relntio11ship, finn11cial, comment fleet equipment and manufacturingtraining. T7re aim of study is empiric research and kind of study is explanatory surve;.1Tire result of this study shaws X weakness sudz as reputation variable, on time sclredule variable,selling puma service and financial support. Based on existing X condition and strategic are impossibleto gain the competition. Therefore, adaptation analysis is needed in SWOT analysis. Newstrategic proposed focus on "dreap price and operation cost" with alliance business such as nontraditionalcontract, equihj investment or joint rienture.Ket; word: Buying business attitude, perfomumce, relationship, financial, common fleet equipment,strategic focus, and strategic adaptation.